2008
DOI: 10.4153/cjm-2009-027-x
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Separating Invariants

Abstract: We prove a characteristic free version of Weyl's theorem on polarization. Our result is an exact analogue of Weyl's theorem, the difference being that our statement is about separating invariants rather than generating invariants. For the special case of finite group actions we introduce the concept of cheap polarization, and show that it is enough to take cheap polarizations of invariants of just one copy of a representation to obtain separating vector invariants for any number of copies. This leads to upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Weyl's theorem no longer holds in positive characteristic, though a weaker statement is still true [12]. However, an analogue of Weyl's theorem, for separating invariants, is true in arbitrary characteristic [6]-and, again, implies the last statement of Proposition 1.…”
Section: Proposition 1 If P ≥ Q Then C(m P ) ≥ C(m Q ) If In Additimentioning
confidence: 90%
“…Weyl's theorem no longer holds in positive characteristic, though a weaker statement is still true [12]. However, an analogue of Weyl's theorem, for separating invariants, is true in arbitrary characteristic [6]-and, again, implies the last statement of Proposition 1.…”
Section: Proposition 1 If P ≥ Q Then C(m P ) ≥ C(m Q ) If In Additimentioning
confidence: 90%
“…Consequently, it is noteworthy that for any positive characteristic and finite group H, the algebra of vector invariants H k[M n,d ] is contained in the p-root closure of the polarizations of the invariants of a single vector. This result follows immediately from Theorem 2.15 in [14] (whose proof is valid in any characteristic) and Theorem 6 above or from Theorem 2.4 in [9] and Theorems 2(c) and 6 above. In stating these results, ])).…”
Section: Saturated Subgroupsmentioning
confidence: 59%
“…This theorem is not true when char k = p > 0; a simple example when H is a torus is given below in Section 2; the case where H is a finite group whose order is divisible by p, was considered by Richman [18]; Domokos, et al, have given examples involving the classical groups [2], [3], [4], [5]. Recently, Draisma, Kemper and Wehlau have shown that at least a set of separating invariants can be obtained by polarization [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they are "really" about separating invariants, in the sense that they have no analogues for generating invariants, even in characteristic zero. From the point of view of polarizations, our results can be viewed as an addendum to [6] making possible some computational simplifications in the construction of a separating set in k[W ⊕ V m ] G for large m. Namely, one takes a separating set S 0 in k[W ⊕ V n ] G with n = dim(V ). Then it is sufficient to take those polarizations of the elements of S 0 that depend only on 2n (resp., n + 1 for reductive G) type V variables to get a (multihomogeneous) separating set in k[W ⊕ V m ] G .…”
Section: Discussionmentioning
confidence: 99%